200k views
1 vote
Owen simplified the expression r-8 s-5.


r−8s−5 =  1r8  ⋅ s5 =  s5r8

User Nitt
by
5.8k points

2 Answers

2 votes

Sample Response: Each base must be treated separately. Since each base is raised to a negative exponent, they should both be in the denominator of the fractions. The simplified form of the expression has 1 in the numerator and r to the 8th power times s to the 5th power in the denominator.

User CasualT
by
5.4k points
4 votes

r⁻⁸ s⁻⁵

using the rule x⁻ⁿ=1/xⁿ

r⁻⁸ s⁻⁵ = (1/r⁸)(1/s⁵)

User Nistor Cristian
by
5.9k points